Vallejo’s Relation to Kierkegaard Reconsidered from the Posthumous Poetry - Zelada Pierrend, Manuel Andrés (2019)
This paper analyzes the points of contact between César Vallejo and Søren Kierkegaard with special emphasis on the posthumous poetry of the Peruvian poet (1923-1938). Such emphasis allows us to explore the relationship between the two beyond the theme of existential anguish, widely discussed by critics. Our proposal is that Vallejo's posthumous work presents a formal and content parallelism with many of the ideas of the Danish philosopher, which reveals a critical stance towards the respective socio-cultural context of both authors. We argue that the relationship between Vallejo and Kierkegaard is not limited to the existential nuance of their work, but should be thought from the role of both authors as social critics. Our analysis begins with the life of both authors, the possibility of a direct reading of Kierkegaard by Vallejo, and the biographical similarities; then, we dwell on the author's posthumous poems, namely, Poemas humanos and España, aparta de mí este cáliz; and finally, we offer our final reflections resulting from the analysis.